2020
DOI: 10.1016/j.heliyon.2020.e03197
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of newly formulated functional instant soup mixtures as dietary supplements for elderly

Abstract: Healthy diet for elderly not only provides them with their needs from macro and micronutrients but also help preventing and treating age-related disorders including non-communicable diseases. So, the present study established to evaluate physical, sensory, chemical and biological characteristics of newly formulated functional instant soup mixtures as dietary supplements for elderly. Lyophilized chickpea, some vegetables and some byproducts (at 5% and 10%) were incorporated in the preparation of two instant sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 65 publications
1
18
1
1
Order By: Relevance
“…Intermediate pH values were observed for F8, F6 and F1 which were not significantly different in between and were significantly different from other soup mixtures. These results are consistent with the results of Mohamed et al (2020) found that there were non-significant changes in the pH value of vegetable soup processed with water or whey. Also, they found that the pH value of all treatment (that is consists of cauliflower, green pea and carrot in different ratios and boiled in different ratios of water and whey) ranged from 5 to 6.68.…”
Section: Physiochemical Characteristics Of Different Soup Mixturessupporting
confidence: 92%
“…Intermediate pH values were observed for F8, F6 and F1 which were not significantly different in between and were significantly different from other soup mixtures. These results are consistent with the results of Mohamed et al (2020) found that there were non-significant changes in the pH value of vegetable soup processed with water or whey. Also, they found that the pH value of all treatment (that is consists of cauliflower, green pea and carrot in different ratios and boiled in different ratios of water and whey) ranged from 5 to 6.68.…”
Section: Physiochemical Characteristics Of Different Soup Mixturessupporting
confidence: 92%
“…Administration of all the prepared beverages reduced the final body weight and body weight gain compared with the metabolic syndrome control and normal control rats. It was observed in a previous study ( Mohamed et al., 2020a ) that foods rich in dietary fiber reduced the body weight gain in rats. Hence, the richness of almond, carrot, quinoa seeds, oat, and banana (the components of the prepared beverages) with dietary fiber as confirmed by Bolling et al.…”
Section: Resultsmentioning
confidence: 79%
“…ab, b, bc, c, d, and e < 0.05 versus control group olive oil reduced AChE activity, MDA, and NO in rats treated with aluminum chloride. It was found that adding olive oil to food contributes to reducing MDA in the brain of geriatric rats, which contributes to protection from brain impairment (Mohamed et al, 2020). Liu et al (2021) concluded that olive oil, as an essential component of the Mediterranean diet, protects against oxidative injury of brain and Alzheimer's disease in humans.…”
Section: F I G U R Ementioning
confidence: 99%